Clinical laboratory analytes and platelet-associated parameters as surrogate markers of subclinical inflammation in latent tuberculosis infection - Selvavinayagam, Sivaprakasam T.; Anusree, Adukkadukkam; Yong, Yean K.; Sankar, Sathish; Frederick, Asha; Rajeshkumar, Manivannan; Kumar, Masilamani S.; Sampath, Palani; Sankar, Ganga; Roy, Chitrali L.; Karishma, Sree J.; Murugesan, Amudhan; et al. (Frontiers in Immunology, 2025)
BackgroundThe global burden of latent tuberculosis infection (LTBI), with one-third of the population, poses a significant challenge in the diagnosis and treatment of TB. Household contacts (HHCs) of active TB-infected individuals are one of the major high-risk groups for whom early screening and timely intervention are highly critical to interrupt TB transmission. The subclinical latent infection transitions into active TB disease due to multiple factors. Laboratory diagnostic markers inherent to interferon-gamma release assay (IGRA) positive and negative HHCs may help predict the risk of LTBI and subsequent reactivation. The study aims to identify biochemical and hematological diagnostic markers associated with HHCs and their IGRA status, and to explore the likelihood of clinical laboratory analytes and platelet-associated parameters for use as surrogate markers of subclinical inflammation in LTBI.MethodsA cross-sectional study was carried out on the HHCs of active TB-infected individuals and healthy controls to determine the association of biochemical and hematological markers with their IGRA status. Blood samples collected from the participants were tested for different laboratory parameters and analyzed by binary regression analysis to determine their efficacy in predicting the development of LTBI.ResultsErythrocyte sedimentation rate (ESR), mean platelet volume (MPV), D-dimer, platelet-large cell ratio (P-LCR), and platelet distribution width (PDW) were significantly high among LTBI-positive individuals. Among different markers, significant association with LTBI was observed with ESR, PDW, and P-LCR, with their AUC and p values reported as 0.6950 (p=0.0095**), 0.7333 (p=0.0469*), 0.7150 (p=0.0042**), respectively. Binary regression analysis revealed significantly higher odds of LTBI in individuals with elevated ESR (OR = 3.05), PDW (OR = 4.67), MPV (OR = 3.5), and P-LCR (OR = 7.67).ConclusionOur study demonstrated clinical laboratory parameters and platelet indices as useful surrogate markers of subclinical inflammation associated with LTBI.